Phyllosticta taxa (Botryosphaeriales, Phyllostictaceae) from northern Thailand and southern European Russia: New host and geographical records - Gomdola, Deecksha; Jayawardena, Ruvishika S.; Mckenzie, Eric H.c.; Bulgakov, Timur S.; Wanasinghe, Dhanushka N.; Huanraluek, Naruemon; Hyde, Kevin D. (Phytotaxa, 2024)
Phyllosticta is a cosmopolitan group of fungi found on various host plants, occurring as pathogens, endophytes and saprobes. Diseases caused by Phyllosticta commonly include leaf and fruit spots that can affect economically important plants. The genus is characterized mainly by aseptate and hyaline conidia and ascospores. Its conidia are surrounded by a mucilaginous sheath, with a single mucoid apical appendage while ascospores exhibit a mucoid cap at both ends. Given that many Phyllosticta taxa are cryptic and share similar morphologies, it is arduous to depict taxonomically relevant characters solely on the basis of morphological or ecological features. Coupled with morphological description, multi-locus phylogenetic analyses of species comprising complexes are used to broadly describe this genus and understand species boundaries. Despite several published taxonomic revisions and enumerations of Phyllosticta species, there is still considerable confusion when identifying these taxa. Herein, we establish three new host records for P. capitalensis, and one new geographical record for P. musaechinensis in Thailand, and one new host and geographical record for P. citribrasiliensis in Russia. We provide an updated phylogenetic tree based on several gene markers: ITS, LSU, ACT, GAPDH, RPB2, and TEF-1α. This includes all Phyllosticta species for which sequence data is available. Six individual Phyllosticta species complexes are accepted. In addition, we synonymize P. ericarum with P. citribrasiliensis.